Psychopathy-related traits and the use of reward and social information: a computational approach - Brazil, Inti A.; Hunt, Laurence T.; Bulten, Berend H.; Kessels, Roy P.; De Bruijn, Ellen R.; Mars, Rogier B. (Frontiers in Psychology, 2013)
Psychopathy is often linked to disturbed reinforcement-guided adaptation of behaviour in both clinical and non-clinical populations. Recent work suggests that these disturbances might be due to a deficit in actively using information to guide changes in behaviour. However, how much information is actually used to guide behaviour is difficult to observe directly. Therefore, we used a computational model to estimate the use of information during learning. Thirty-six female subjects were recruited based on their total scores on the Psychopathic Personality Inventory (PPI), a self-report psychopathy list, and performed a task involving simultaneous learning of reward-based and social information. A Bayesian reinforcement-learning model was used to parameterize the use of each source of information during learning. Subsequently, we used the subscales of the PPI to assess psychopathy-related traits, and the traits that were more strongly related to the model’s parameters were isolated through a formal variable selection procedure. Finally, we assessed how these covaried with model parameters. We succeeded in isolating key personality traits believed to be relevant for psychopathy that can be related to model-based descriptions of subject behaviour. Use of reward-history information was negatively related to levels of trait anxiety and fearlessness, whereas use of social advice decreased as the perceived ability to manipulate others and lack of anxiety increased. These results corroborate previous findings suggesting that sub-optimal use of different types of information might be implicated in psychopathy. They also further highlight the importance of considering the potential of computational modelling to understand the role of latent variables, such as the weight people give to various sources of information during goal-directed behaviour, when conducting research on psychopathy-related traits and in the field of forensic psychiatry.